Analysis of English Learning Difficulty of Students in Elementary School - Sintadewi, Ni Made Dita; Artini, Ni Putu Juni; Febryan, Irwan (Universitas Pendidikan Ganesha, 2020)
The low student learning outcomes are caused by students' thought that English is a difficult and boring subject so that students have difficulties understanding it. The purpose of this study is to analyze the types of learning difficulties experienced by students, the factors that affect learning difficulties, and to find out the efforts to overcome the difficulties of learning English in grade V of Elementary School. This research method uses descriptive qualitative. The research subjects were 22 grade V students and grade V teachers. The data collection procedures used were interviews, questionnaires, and documentation. Data analysis used is a qualitative approach. The results of this study were 16 students experienced difficulty learning English, and also did not understand when the teacher delivered English materials. The factors that cause difficulty in learning English for grade V students are internal factors, including students are still less motivated and less interested in taking English lessons, while the external factor is that the teacher does not use teaching aids and the methods used are less varied and not innovative. Based on the above results, it is showed that grade V Elementary School students still have difficulty learning English lessons. Therefore, it can be concluded that students' learning concerns will have an impact on low learning outcomes